Mapping South American Promises: Potosí, Brazil, and European Visions - Doré, Andréa (Early Modern History and Modern History E-Books Online, Collection 2025., 2025)
"Nomen est omen". A name is a prophecy, a destiny, or even a promise. Why was South America once referred to as Peru, "Peruana", or "América Peruana"? What role did the Potosí Mountain play in shaping these designations? And how did these perceptions affect the lands of Brazil? This book offers new insights into these questions, exploring both the continuities and the shifts in European representations of South America. It reveals how, in the first two centuries of its history, Brazil compensated for the scarcity of gold and silver with brazilwood, sugar, the labor and souls of its indigenous peoples, the toil of enslaved Africans, and its geography.